2001
DOI: 10.1080/019262301753178500
|View full text |Cite
|
Sign up to set email alerts
|

CB6F1-rasH2 Mouse: Overview of Available Data

Abstract: This article presents data from short-term carcinogenicity studies of compounds tested in the CB6F1-rasH2 transgenic mouse as part of the International Life Sciences Institutes' (ILSI) Health and Environmental Sciences' (HESI) Alternative to Carcinogenicity Testing (ACT) project. Additionally, data from other studies that were not conducted as part of the ILSI program, but used comparable or slightly modi ed protocols, are included here. A signi cant number (3 of 4) of the genotoxic carcinogens tested were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
104
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 18 publications
(30 reference statements)
3
104
0
1
Order By: Relevance
“…Hence, nearly half of the time, these animal models failed to identify human carcinogens, which does not inspire confidence in their capability to screen for the human carcinogenicity of pharmaceuticals in drug regulation. By contrast, the animal models in the ACT study correctly identified 83% of compounds that were both human non-carcinogens and rodent carcinogens and 100% of the compounds that were non-carcinogens in both humans and rodents (Eastin et al 2001;Storer et al 2001;Usui et al 2001;van Kreijl et al 2001).…”
mentioning
confidence: 99%
“…Hence, nearly half of the time, these animal models failed to identify human carcinogens, which does not inspire confidence in their capability to screen for the human carcinogenicity of pharmaceuticals in drug regulation. By contrast, the animal models in the ACT study correctly identified 83% of compounds that were both human non-carcinogens and rodent carcinogens and 100% of the compounds that were non-carcinogens in both humans and rodents (Eastin et al 2001;Storer et al 2001;Usui et al 2001;van Kreijl et al 2001).…”
mentioning
confidence: 99%
“…On the other hand, there is some evidence that the TgHras2 mouse model (rasH2 mouse model), a transgenic mouse over-expressing the human proto-oncogene, c-Ha-ras, can detect nongenotoxic as well as genotoxic carcinogens 28 . Hemangioma and hemangiosarcoma, which are commonly observed in mice chronically treated with PPAR γ and dual agonists, are observed at higher incidence as spontaneous tumors in rasH2 mice 26 . Mitsumori et al recently reported increased incidences of hemangioma and hemangiosarcoma in rasH2 mice after 26-week treatment with troglitazone, a PPAR γ agonist 2 9 .…”
Section: Usefulness Of Transgenic Animal Modelsmentioning
confidence: 99%
“…The ICH 1B guideline 15 defines several transgenic mouse assays including the p53+/-deficient model 24 , Tg.AC model 25 , TgHras2 model 26 , and Xpa deficient model 27 as alternative methods for additional in vivo testing of carcinogenicity. Although the FDA has recommended the p53+/-deficient mouse model as an alternative for 2-year carcinogenicity study, the p53+/-deficient mice model is not be applicable to carcinogenicity assessment of PPAR agonists, since non-genotoxic compounds are undetectable in this model and PPAR agonists generally yield negative results in the standard genotoxicity studies.…”
Section: Usefulness Of Transgenic Animal Modelsmentioning
confidence: 99%
“…Based on previous studies, it is well recognized that rasH2 mice are very susceptible to genotoxic carcinogens; therefore, they are generally accepted as an alternative animal model and used in place of long-term carcinogenicity tests (Yamamoto et al, 1996;Usui et al, 2001;Morton et al, 2002). On the other hand, since rasH2 mice cannot always detect all types of carcinogens, it is necessary to validate the carcinogenic susceptibility of these mice to various chemicals for appropriate evaluation of carcinogenic substances.…”
Section: Introductionmentioning
confidence: 99%